A Netnography Analysis of Thematic Hadith Memes Distribution on Social Media - Usman, Ermawati; Nurdin, Nurdin; Ahmed, Ashir; Huda, Miftachul (Pascasarjana IAIN Pontianak, 2023)
Instead, the use of hadith memes among Muslim communities is rampant, and the study of hadith memes is scarce. This study, therefore, aims to examine the use of hadith memes by millennial Ulama and the types and content of hadith memes disseminated and exchanged in the virtual world by millennial Ulama. This study built thematic hadith memes based on their contents and formats on social media platforms using Rajan's (2015) theory of religious memes. This study employed a netnography method, collecting data from the social media sites Facebook and WhatsApp of Islamic millennial Ulama. We used a thematic approach in analyzing the data. Our results show that hadith memes disseminated on social media sites fall into four themes. The first theme is prayer hadith memes that present the traditions of prayers in Islam. The second theme is hadith memes related to sacrifice, which depict messages of Muslims' willingness to practice gratitude and to sacrifice to do things according to Allah's will. The third theme of the hadith memes is that they present messages about the afterlife, which tells about the end of life, such as life in the grave, hell, and heaven. The last theme is hadith memes about tolerance, which tell about the importance of living in tolerance and respecting each other. We conclude that our study contributed to understanding the distribution of hadith meme themes in the virtual world to enhance the sharing and exchange of Islamic teachings.